Managing waste in refurbishment projects in Klang Valley - Chai, Kok Liong; Azlan Shah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Waste has been a major problem in the construction industry. Not only waste has an impact on the efficiency of construction industry but it also causing negative impact to the environment and moreover the total project cost. There are a lot of researches on sustainable construction industry but not they are not related it with refurbishment project in details. Parties involve in refurbishment project encounter numerous causes of waste generation and uncertainty in managing waste. This papers aims to identify variable that contribute to waste in refurbishment projects and implementation of effective waste management in construction industry. A questionnaire survey to 172 respondents has conducted to several professions in refurbishment projects. The methodologies used are by survey. Through survey and analysis processes, all the collected data were analyzed using quantitative statistical analysis package software. The correlation tests between the dependent, intervening and independent variables would determine the relationships among of the group of variables shown in theoretical framework. Once the survey revealed waste contribution factors and the effectiveness of waste, a set of findings and recommendations are proposed for better handling waste management in refurbishment projects. The recommendation listed out and discussed will enhance the waste minimization for the construction industry and hopefully the readers of this research could find something useful information for their own ongoing or future refurbishment projects.